DAUR ULANG SAMPAH ORGANIK DAN UNORGANIK BERNILAI EKONOMIS - Hamid B., Abdul; Esti, Erna Atiwi Jaya; Muddarisna, Nurul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
Waste is thing that can pollute the environment and become a source of disease in the community. With the pace of population growth, it is increasingly triggering the amount of waste produced by the community in each day, both organic and unorganic waste so that there was garbage dumping everywhere as happened in neighborhood Association 03 and 02 citizens Association: 04 Kemantren Village, Jabung District, Malang Regency. To overcome this problem, the PKM implementation team of Community Partnership Program had carried out activities, namely (1) counseling on the importance of creating a clean and comfortable environment, (2) training in recycling organic and non-organic waste into economic value goods (3) providing assistance in marketing the results of recycling organic and inorganic waste. The results of these activities were (1) growing public awareness in creating a clean environment, (2) the community could made compost from organic waste and compuser liquid (3) the community could make souvenirs from inorganic waste, and (4) Small Business and Intermediate was surrounded in Kemantren Village, Jabung District Malang Regency